PENGALAMAN KOMUNIKASI DALAM BERADAPTASI DENGAN HOSTCULTURE (STUDI PADA PROSES ADAPTASI MAHASISWA ETNIS BATAK DI KOTA SEMARANG) - Dimas Obwid Robertus Belarmino Malau; Turnomo Rahardjo; Triyono Lukmantoro (Interaksi Online, 2023)
Individuals pursuing studies outside their native cultural environment demand complex adaptation. Migration to a culturally distinct environment propels cross-cultural adaptation and communication, especially in Semarang which attracts diverse students, including those from the Batak ethnic group. In this context, cross-cultural communication, particularly with Javanese culture, becomes essential in Semarang's culturally diverse setting. This research examines the cultural adaptation of Batak ethnic students within the host culture during their educational journey in Semarang. The employed method is qualitative, grounded in the interpretive paradigm and phenomenological approach. Data for this study were obtained through in-depth interviews with four Batak ethnic students aged 18 and above, who had not previously resided in Semarang. The findings of this research reveal that the cultural adaptation of Batak ethnic students in Semarang follows several stages based on the U-Curve model. The stages experienced by Batak ethnic students in adapting to the new culture encompass entering the new culture, culture shock, adjustment to the new culture, and understanding the core of the new culture. In the first stage, Batak ethnic students encounter differences in values, norms, language, and lifestyle compared to Javanese culture, resulting in mixed feelings of excitement and enthusiasm, as well as anxiety stemming from unfamiliarity with the new environment. The second stage, termed as the culture shock phase, marks a period where feelings of alienation and discomfort start to arise due to significant cultural disparities, such as language, communication style, and cuisine. However, through effort and time, Batak ethnic students successfully transition into the adjustment phase, where they learn and adapt to new customs, including mastering Javanese language for daily interactions. In this stage, support from local peers plays a pivotal role in aiding Batak ethnic students to adapt more effectively. This adjustment process varies in duration, ranging from two weeks to six months. Ultimately, by grasping the essence of the new culture, Batak ethnic students feel more at ease and adept at functioning within Javanese culture. Understanding the language, customs, and local norms assists in overcoming anxiety and enhances comfort in interacting with the local community. Anxiety also emerges as a factor faced by Batak ethnic students during the adaptation process, primarily due to uncertainty in encountering unfamiliar culture, lack of peers from the same hometown, and a sense of longing for their place of origin.